(untitled) (Journal of Engineering, 2013)
The evacuated tube solar collector ETC is studied intensively and extensively by experimental and theoretical works, in order to investigate its performance and enhancement of heat transfer, for Baghdad climate from April 2011 till the end of March 2012. Experimental work is carried out on a well instrumented collector consists of 16 evacuated tubes of aspect ratio 38.6 and thermally insulated tank of volume 112L. The relation between convective heat transfer and natural circulation inside the tube is estimated, collector efficiency, effect of tube tilt angles, incidence angle modifier, The solar heating system is investigated under different loads pattern (i.e closed and open flow) to evaluate the heat loss coefficient from tank and tubes, test the collector with various aspect ratios (32.9 and 27.2). The enhancement in collector performance is studied by using two reflectors (Flat Plate and Curved Plate) and nanofluid (Water-AL2O3).Theoretical work is run by software (Fluent 6.3), to compute the velocity and temperature profiles within the tube, for different tube diameters, effect of tube junction angle and stagnant region in the bottom of the evacuated tube. The experimental results shows that the heat loss coefficient for tube is W/m2.K and for tank is W/m2.K, the maximum collector temperature is 79°C in winter and 99°C in summer, while that belong to nanofluid collector is 99°C in winter. The best tilted angle (optimum) of evacuated tube is 41° annually. The collector efficiency increased when using nanofluid of (1, 0.6, 0.3)% volume fraction as(28.4, 6.8, 0.6)% respectively. The efficiency decreases as (33, 62)% when decreasing tube aspect ratio from 38.6% to 32.9% and 27.2% respectively. An increase of (16.9 and 7.08)% in collector efficiency is obtained when using curved and flat plate reflectors respectively. From simulation the best junction angle of the tank is 22.5°. The stagnant region is influenced with changing heat flux, tilted angle and aspect ratio.